Perancangan Pengalaman Pengguna Aplikasi Pemesanan Vendor Acara Pernikahan berbasis Mobile menggunakan Metode Human Centered Design - Naufal Hilmy; Riswan Septriayadi Sianturi; Agi Putra Kharisma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The number of weddings in Indonesia makes it difficult for people who will hold a wedding to find the vendor of their choice. As recorded by the Indonesian statistical report, there were 1.74 million weddings throughout 2021. However, most people ordering wedding vendors are still manual, such as searching through Instagram or asking other people for information about wedding vendors. This research aims to design the user experience of wedding event vendor ordering applications to help between consumers who are getting married and wedding event vendors. The method used to design the user experience in this research is using Human-Centered Design. With this method, researchers can prioritize user needs by carrying out several stages, like literature study, user context analysis, user needs analysis, solution of design, and solution design evaluation. The final results of this research are wireframes, mockups, and prototypes which are then tested using usability testing on 5 respondents from the vendor side and 5 respondents from the consumer side. The test results from the consumer side include the effectiveness value of 100%, the efficiency value of 0.104 goals/second, the satisfaction value of 80 in the Good category and grade B scale. Meanwhile, from vendor users, the effectiveness value is 97.14%, the efficiency value is 0.071 goal/second, the satisfaction value is 82.5 with Excellent category and grade B scale.